Generation of a new Paneth cell–specific Cre-recombinase transgenic mouse line - Natalia Garcia-Gonzalez; Natalia Garcia-Gonzalez; Charlotte Wallaeys; Charlotte Wallaeys; Wendy Toussaint; Wendy Toussaint; Tino Hochepied; Tino Hochepied; Sylviane Dewaele; Sylviane Dewaele; Somara De Beul; Somara De Beul; et al. (Frontiers in Immunology)
Paneth cells are located in the crypts of Lieberkühn in mammalian small intestines and are producing antimicrobial peptides to keep the microbiome under control. The genetic manipulation of Paneth cells and their tracking and depletion depend on a solid Paneth cell–specific Cre-transgenic line. Here, we describe bulk RNA sequencing (RNA-seq)–based expression data from pure, sorted Paneth cells of C57BL/6J mice and identify several strongly expressed Paneth cell–specific genes, the expression of which is stable under pathophysiological conditions, as well as in the duodenum, jejunum, and ileum. We selected the Defa24 gene regulatory sequences and generated a new Defa24iCre transgenic line using BAC technology, Tg(Defa24-icre)Cli. The resulting transgenic line provides robust expression and allows for the complete depletion of Paneth cells by cell ablation, yielding mice without any detectable lysozyme biological activity in the small intestines.